Criticality, identity, and ethics: Toward the construction of ethical subjectivity in applied linguistics research. (March 2022) - Shin, Jaran
Abstract: Criticality has become legitimate and prominent in the field of applied linguistics. Given the realities of our uncertain and worrying times, however, it is essential to consider (a) how criticality can move beyond the rhetoric of inclusion, social transformation, and justice, and (b) the direction(s) in which critical applied linguistics research must point. This paper conjoins criticality, identity, and ethics and proposes the construction of ethical subjectivity as a way to reorient applied linguistics research toward the public good. Drawing on Foucault's later work, I contend that the process of becoming an ethical subject, which involves both internal and external transformations, would create alternative spaces and ways of action—giving new momentum to the project of realizing the world we wish to live in together.